Internal Auditor Human Resources Development Strategy in the Era of Disruption - Y Ony Djogo (Atestasi : Jurnal Ilmiah Akuntansi, 2023)
The development of digital technology has brought significant changes in business paradigms and audit practices in companies. This research aims to explore and analyze internal auditors' human resource (HR) development strategies in facing the challenges of the era of disruption. This research uses a qualitative approach with descriptive methods. The research results highlight that internal auditor competency is very important in facing the challenges of the era of digital disruption and transformation. It was found that strong communication skills, critical thinking abilities, and a broad business view are the keys to auditors' success in conveying audit findings effectively and providing strategic insights. In addition, emotional intelligence has been shown to have a significant role in managing conflict and maintaining a balance between objectivity and sensitivity to other people's feelings. Professional skepticism has proven to be a key foundation for a thorough and prudent audit approach. Human resource development strategies, through continuous training, technology empowerment, improving critical and analytical skills, developing soft skills, as well as implementing reward systems, were identified as crucial steps to ensure that auditors not only have superior technical skills, but also become strategic partners who can support the company's long-term growth.